2020
DOI: 10.3389/fmed.2020.00110
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus as Rescue Therapy for Refractory/Relapsed Immune Thrombocytopenia: Results of a Single-Center, Prospective, Single-Arm Study

Abstract: Immune thrombocytopenia (ITP) is an autoimmune disease which arises due to self-destruction of circulating platelets. Failure to respond or maintain a response to first-line treatment can lead to refractory/relapsed (R/R) ITP. The mechanism remains complicated and lacks a standard clinical treatment. Sirolimus (SRL) is a mammalian target of rapamycin (mTOR) inhibitor that has been demonstrated to inhibit lymphocyte activity, indicating potential for SRL in treatment of ITP. Activation of the mTOR pathway in au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 31 publications
1
24
1
Order By: Relevance
“…Recently, sirolimus has shown some promise for treatment of relapsed/refractory ITP, with a response rate of 85% in ITP patients after 3 months of treatment and 75.6% in patients with ITP or other autoimmune cytopenias after a median of 14 months’ treatment and 18 months’ follow‐up; treatment was generally well tolerated. 50 , 51 The combination of danazol plus all‐trans retinoic acid was recently evaluated in a phase 2 trial for second‐line management of adults with primary ITP. After 52 weeks of follow‐up, 38% of patients (20/45) achieved complete response versus 8% of patients (4/48) receiving danazol alone.…”
Section: Alternatives To Corticosteroidsmentioning
confidence: 99%
“…Recently, sirolimus has shown some promise for treatment of relapsed/refractory ITP, with a response rate of 85% in ITP patients after 3 months of treatment and 75.6% in patients with ITP or other autoimmune cytopenias after a median of 14 months’ treatment and 18 months’ follow‐up; treatment was generally well tolerated. 50 , 51 The combination of danazol plus all‐trans retinoic acid was recently evaluated in a phase 2 trial for second‐line management of adults with primary ITP. After 52 weeks of follow‐up, 38% of patients (20/45) achieved complete response versus 8% of patients (4/48) receiving danazol alone.…”
Section: Alternatives To Corticosteroidsmentioning
confidence: 99%
“…Treg cells inhibit the expression of IL-17 by secreting IL-10 and TGF-β, which plays an immunosuppressive role [19]. Studies have demonstrated that the imbalance of Treg/Th17 cells is involved in ITP pathogenesis and inhibition of Th17 cell differentiation can ameliorate ITP [4,[20][21][22]. Similarly, in our study, Th17 cells were up-regulated and Treg cells were down-regulated in CD4 + T cells from ITP patients compared with the NC group, indicating that the increase of Th17 cells resulted in an increased inflammatory response and a weakened immunosuppression function, further promoted the onset of ITP.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in patients who responded, SRL treatment was associated with a reduction in the percentage of Th2, Th17 cells, and increase in the percentage of monocytic-Myeloid-Derived Suppressor Cells (M-MDSCs) and T regulatory cells (Tregs), indicating that SRL may re-establish peripheral tolerance. To date, this is the largest prospective study to date evaluating SRL as a rescue therapy in patients with R/R ITP ( 105 ). ITP is a heterogeneous disease with a complex pathobiology; based on our experience and others’, we believe that mTORi can be effective in treating refractory ITP, but more randomized controlled trials (RCTs) are needed to support these observations.…”
Section: Applications In Non-malignant Hemopathiesmentioning
confidence: 99%
“…Sirolimus has benefited patients with primary autoimmune cytopenias, possibly by stimulating Tregs ( 105 , 106 ). In the pathogenesis of AIHA, increased expansion or function of Treg cells can inhibit the over-activation of effector T cells and other immune cells, thus regulating the production of excess RBC antibodies ( 107 , 108 ).…”
Section: Applications In Non-malignant Hemopathiesmentioning
confidence: 99%